1998
DOI: 10.1007/s004010050870
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Alzheimer-type neuropathology in Creutzfeldt-Jakob disease

Abstract: Creutzfeldt-Jakob disease (CJD) and Alzheimer's disease (AD) share clinical, neuropathological, and pathogenetic features. To investigate eventual mutual influences, we screened prominently affected neocortex from 110 neuropathologically proven CJD patients for Alzheimer-type pathology with anti-beta/A4, Bielschowsky and anti-tau (immuno)stains. The neuropathological classification of Alzheimer-type pathology was made according to the CERAD criteria. Results were controlled by comparison with Alzheimer-type ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 20 publications
7
112
0
Order By: Relevance
“…Coexisting AD pathology has been described in CJD. In an Austrian neuropathological longitudinal study of 110 CJD patients, coexisting AD pathological changes have been described in 11% of cases of which 20% showed NFT pathology [6]. Another study reported NFT pathology in 19% of 65 sporadic CJD patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Coexisting AD pathology has been described in CJD. In an Austrian neuropathological longitudinal study of 110 CJD patients, coexisting AD pathological changes have been described in 11% of cases of which 20% showed NFT pathology [6]. Another study reported NFT pathology in 19% of 65 sporadic CJD patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Deposition of both PrP sc and Ain the central nervous system (CNS) results in neurodegeneration. Moreover, the coexistence of Aand PrP sc amyloid deposits in affected brains, although controversial, has been widely reported (Barcikowska et al, 1995;Debatin et al, 2008;Ferrer et al, 2001;Hainfellner et al, 1998;Leuba et al, 2000;Tsuchiya et al, 2004). In addition, a recent study indicates that PrP c may participate in the removal of A oligomers, which would implicate PrP c in AD (Charveriat et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…AD and CJD share a variety of neuropathological features (7)(8)(9), and the Val/Met-129 polymorphism in the gene encoding PrP C has been identified as a risk factor for early onset AD (10,11). In addition, like APP, PrP C is shed from the cell surface by zinc metalloproteases and is subject to endoproteolysis by ADAM10 and ADAM17 (12)(13)(14)(15).…”
mentioning
confidence: 99%